2011
DOI: 10.1590/s1415-47572011005000033
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of scattered populations of the Indian eri silkworm, Samia cynthia ricini Donovan: differentiation of subpopulations

Abstract: Deforestation and exploitation has led to the fragmentation of habitats and scattering of populations of the economically important eri silkworm, Samia cynthia ricini, in north-east India. Genetic analysis of 15 eri populations, using ISSR markers, showed 98% inter-population, and 23% to 58% intra-population polymorphism. Nei’s genetic distance between populations increased significantly with altitude (R2 = 0.71) and geographic distance (R2 = 0.78). On the dendrogram, the lower and upper Assam populations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…An. yamamai is an important insect resource for the agricultural industry in Asia, including South Korea, but no population genetic information is available for its domestic or foreign populations (Liu et al, 2010;Pradeep et al, 2011;Singh et al, 2012). Inferring the population genetic structure of this species would be important for systematic domestication and subsequent cocoon production, along with the traditional perspectives to understand the evolutionary process of the populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An. yamamai is an important insect resource for the agricultural industry in Asia, including South Korea, but no population genetic information is available for its domestic or foreign populations (Liu et al, 2010;Pradeep et al, 2011;Singh et al, 2012). Inferring the population genetic structure of this species would be important for systematic domestication and subsequent cocoon production, along with the traditional perspectives to understand the evolutionary process of the populations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the wild and domesticated populations of A. assamensis from India have been studied to estimate their genetic diversity using inter-simple sequence repeats (ISSR) and simple sequence repeats (SSR, Singh et al, 2012). In the eri silkworm, Samia cynthia ricini, found in Northeast India, ISSR markers have been employed to estimate the genetic structure of its unexploited, scattered populations at various altitudes, as well as the genetic interactions among its patchy subpopulations (Pradeep et al, 2011). Using limited samples, Liu et al (2010) investigated the genetic diversity and genetic structure of B. mori, A. pernyi, and Samia cynthia ricini collected in China using randomly amplified polymorphic DNA markers.…”
Section: Introductionmentioning
confidence: 99%
“…The number of fragments by ISSR primer may vary considerably, depending on the species. Some authors [3,[30][31][32][33], observed a total number of bands per primer lower than 10 (about five) with the primers UBC-807, UBC-810, UBC-812, UBC-813, and UBC-856, which were relatively uninformative in their respective analyses. However, other authors, such as NAN et al [27,[34][35][36][37] reported an abundant generation of bands for these same primers, showing an average of 20 fragments per primer.…”
Section: Resultsmentioning
confidence: 99%